ASME 2005 Power Conference 2005
DOI: 10.1115/pwr2005-50051
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Scrubbing for the Removal of Sulfur Dioxide in a Steam Turbine Power Plant

Abstract: The most popular method of controlling sulfur dioxide (SO2) emissions in a steam turbine power plant is a flue gas desulfurization (FGD) process that uses lime/limestone scrubbing. Another relatively newer FGD technology is to use seawater as a scrubbing medium to absorb SO2 by utilizing the alkalinity present in seawater. This seawater scrubbing FGD process is viable and attractive when a sufficient quantity of seawater is available as a spent cooling water within reasonable proximity to the FGD scrubber. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…• Utilization of free seawater and air along with their availability results in a significant reduction in the SW-FGD plant operating costs [20,21].…”
Section: Reliability and Efficiency Of Sw-fgd Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…• Utilization of free seawater and air along with their availability results in a significant reduction in the SW-FGD plant operating costs [20,21].…”
Section: Reliability and Efficiency Of Sw-fgd Processesmentioning
confidence: 99%
“…• Waste disposal is not a concern in the SW-FGD process as it does not generate any waste. This eliminates any cost to be spent on waste disposal, and leads to higher reliability [20,22].…”
Section: Reliability and Efficiency Of Sw-fgd Processesmentioning
confidence: 99%
“…Finally, the liquid waste is cooled down and discharged back to the sea. Compared to the wet limestone process, SFGD has two main advantages: (1) because seawater itself is alkaline (pH 7.5–8.3), alkaline absorbent is not necessary in the scrubber, and (2) the effluent seawater treatment process is much simpler, as only a simple aeration basin is needed to oxidize S(IV) to S(VI), a natural component of seawater. ,, To date, many countries, including Norway, , Malaysia, Indonesia, Saudi Arabia, and China, ,− have installed SFGD technology.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many countries, including Norway, , Malaysia, Indonesia, Saudi Arabia, and China, have installed SFGD technology. The thermal power plants along the coastal area of eastern China, which is highly industrialized and has a high population density, account for one-third of the total thermal power plant output capacity of the entire country.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 Indeed, Tilly et al found seawater scrubbing to be the "best practicable environmental option" among four different desulfurization processes (spray drying, wet limestone, Wellman−Lord, and seawater scrubbing). 6 To date, many countries, including Norway, 7,8 Malaysia, Indonesia, Saudi Arabia, 9 and China, 10−12 have installed SFGD technology. The thermal power plants along the coastal area of eastern China, which is highly industrialized and has a high population density, account for one-third of the total thermal power plant output capacity of the entire country.…”
Section: Introductionmentioning
confidence: 99%